SERUM TESTOSTERONE, EMOTION AND COGNITIVE FUNCTIONING DEFICITS IN PATIENTS WITH ANOREXIA NERVOSA: A TASK SWITCHING STUDY - Gul, Amara; Jamil, Summaira (Journal of Postgraduate Medical Institute, 2018)
Objective: To examine relationship between testosterone, emotional intelligence (EI), affective control and cognitive functioning in patients with anorexia nervosa (AN). Methodology: Fifty women diagnosed with restrictive subtype of AN from Bahawal Victoria Hospital Bahawalpur, Civil Hospital Bahawalpur and Nishtar Hospital Multan from April 2016 to February 2017 and fifty healthy demographically matched women took part in the study. Serum testosterone levels were obtained from medical reports not older than two weeks of the day when testing session was conducted. Participants completed measures of EI, affective control and task switching. Results: Anorexics women showed reduced testosterone level (mean 22.44 ±0.73 ng/dl) as compared to healthy individuals (mean 31.80 ±2.02 ng/dl). Women with AN demonstrated under developed emotional capacity (mean 84.28 ±2.74 vs. 123.30 ±4.79), affective control deficits (mean 4.92 ±1.04 vs. 2.64 ±0.69) and impaired task switching (mean 110.76 ±5.77 vs. 47.66 ±4.62 seconds) in contrast to healthy individuals. Serum testosterone, EI and duration of amenorrhea were found as significant predictors of task switching performance in patients with AN (p<0.001, R2 =.78). Conclusion: Serum testosterone, duration of amenorrhea and emotional intelligence can serve as a marker of impaired cognitive functioning in patients with anorexia nervosa.